2022
DOI: 10.3389/fnut.2022.894686
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Weight-Adjusted-Waist Index With Risk of All-Cause Mortality: A 10-Year Follow-Up Study

Abstract: BackgroundTo explore the relationship between weight-adjusted-waist index (WWI) and the risk of all-cause mortality in one urban community-dwelling population in China.MethodsThis is a prospective cohort study with a sample of 1,863 older adults aged 60 years or over in Beijing who completed baseline examinations in 2009–2010 and a 10-year follow-up in 2020. WWI was calculated as waist circumference (cm) divided by the square root of weight (kg). Cox regression analysis was performed to investigate the signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…To our knowledge, this is the rst report assessing the association between WWI and PAD in a nationally representative population. As a new simple adiposity index, WWI has been investigated in various elds, especially related to cardiometabolic diseases [17][18][19]22 . In a cohort study involving 465,629 individuals, Park et al found that WWI was positively associated with cardiometabolic morbidity and cardiovascular death 16 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the rst report assessing the association between WWI and PAD in a nationally representative population. As a new simple adiposity index, WWI has been investigated in various elds, especially related to cardiometabolic diseases [17][18][19]22 . In a cohort study involving 465,629 individuals, Park et al found that WWI was positively associated with cardiometabolic morbidity and cardiovascular death 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on reviews of the literatures, potential covariates that may confound the association between WWI and AAC were summarized in our multivariable-adjusted models 30 , 33 , 37 , 38 . The covariates in present study included demographic covariates and health condition covariates.…”
Section: Methodsmentioning
confidence: 99%
“…Rahman et al 32 found an increase in BMI was inversely associated with AAC, while there was no statistically significant association between total body and trunk fat percentages and AAC. These contradictory results suggest that the relationship between obesity and AAC remains unclear, using BMI as a criterion for obesity may not be accurate because it could distinguish the fat, muscle mass and abdominal obesity 33 .…”
Section: Introductionmentioning
confidence: 99%
“…The weight-adjusted waist circumference index (WWI), originally proposed by Park et al [ 23 ], was shown to be associated with age-related changes in body composition, such as loss of muscle mass and retention or gain of fat mass [ 24 ]. In addition, several studies have shown a significant positive association between WWI and cardiovascular disease [ 25 27 ], chronic kidney disease [ 28 ], and all-cause mortality [ 29 ].…”
Section: Introductionmentioning
confidence: 99%